Pouzití rychlé aglutinace v sérotypizaci Mycobacterium avium-intracellulare komplexu - Süssland, Z; Hrdinová, V (Veterinarni medicina, 1976)
The authors describe a new method of the typification of mycobacteria by rapid (droplet) agglutination. This technique is of the same specificity as slow agglutination; however, it is simpler and practicable for normally equipped tuberculosis-testing laboratories. It is suitable for the use in typification as one of the differentiating techniques as well as for preliminary differentiation of mycobacteria from primocultures.
Keywords: aglutinace; Antigen-Antibody Complex; Agglutination; zvířata; Mycobacterium avium; sérotypizace; tvorba protilátek; imunokomplex; Antibody Formation; Serotyping; Mycobacterium; Time Factors; časové faktory; Animals